Penggunaan Media Sosial Instagram dalam Strategi Promosi - Agung, Dimas Pandan; Pranoto, Agung; Saputra, Rivaldo Ihzan; Lisrandy, Satria Bayu (Institut Teknologi Pendidikan Indonesia, 2024)
The rapid development of the internet has made the flow of information exchange more practical, which makes people prefer to communicate online, one of which is Instagram social media. Instagram has feature components that are useful for marketing advertisements, has a business account, and has disadvantages such as limited scope, and low upload graphics. The purpose of this research is to find out how the utilization of Instagram social media as a marketing promotion media for pudding in Palembang, what obstacles there are in utilizing Instagram as a marketing advertising media, and what troubleshooting can be done in utilizing Instagram as a marketing advertising media. The research method uses a descriptive approach with a qualitative research type. Data is collected by observation, interview, and documentation. The results showed that using Instagram social media as a medium for pudding marketing promotion in Palembang City has positively impacted @puding.fa_ promotional activities. The obstacles in utilizing Instagram are the lack of ideas and preparation for conducting promotional activities on Instagram. The solution to the obstacles is for @puding.fa_ to form a team to manage their Instagram account and promote their products more actively. For that, @puding.fa_ has Instagram as their promotional media.